Long term effects of bilateral subthalamic nucleus stimulation on cognitive function, mood, and behaviour in Parkinson's disease. Issue 6 (14th May 2004) - Funkiewiez, A; Ardouin, C; Caputo, E; Krack, P; Fraix, V; Klinger, H; Chabardes, S; Foote, K; Benabid, A-L; Pollak, P
Abstract : Background: Long term effects of subthalamic nucleus (STN) stimulation on cognition, mood, and behaviour are unknown. Objective: This study evaluated the cognitive, mood, and behavioural effects of bilateral subthalamic nucleus deep brain stimulation (STN DBS) in patients with Parkinson's disease (PD) followed up for three years. Methods: A consecutive series of 77 PD patients was assessed before, one, and three years after surgery. Mean (SD) age at surgery was 55 (8). Seven patients died or were lost for follow up. Neuropsychological assessment included a global cognitive scale, memory, and frontal tests. Depression was evaluated using the Beck depression inventory. Assessment of thought disorders and apathy was based on the unified Parkinson's disease rating scale. Reports of the behavioural changes are mainly based on interviews done by the same neuropsychologist at each follow up. Results: Only two cognitive variables worsened (category fluency, total score of fluency). Age was a predictor of decline in executive functions. Depression improved whereas apathy and thought disorders worsened. Major behavioural changes were two transient aggressive impulsive episodes, one suicide, four suicide attempts, one permanent apathy, one transient severe depression, four psychoses (one permanent), and five hypomania (one permanent). Conclusions: Comparing baseline, one year, and three year postoperative assessments, STN stimulation did not lead to global cognitive deterioration. Apathy scores mildly increased. Depression scores mildly improved. Behavioural changes were comparatively rare and mostly transient. Single case reports show the major synergistic effects of both medication and stimulation on mood and behaviour, illustrating the importance of a correct postoperative management.